Real versus ideal: Toward a deeper understanding of how coaches gain knowledge - van Woezik, R. (Nipissing University, 2018)
Coaches play a pivotal role in sport participation, performance and fostering developmental outcomes for athletes (Côté & Gilbert, 2009). An `effective` coach is one who enhances the 4 C`s (competence, confidence, connection, character) in athletes by consistently integrating professional, interpersonal, and intrapersonal knowledge into their coaching practices (Côté & Gilbert, 2009). Given that knowledge development is a fluid process, both effective and ineffective coaches can expand their knowledge base by learning through a variety of different sources. In 2008, Erickson and colleagues explored the actual and preferred sources through which coaches gain knowledge. However, with an ever-evolving society (e.g., technology) comes the possibility that sources of coaching knowledge have also evolved. As such, the purpose of this research was to constructively replicate the findings of Erickson et al. (2008) by (a) expanding the knowledge source collection, (b) refining the quantitative method by generating preference data for all knowledge sources, and (c) qualitatively exploring how and why coaches engage with these knowledge sources. This was accomplished using a sequential explanatory mixed-method design involving two complementary studies. In Study 1, 798 coaches (Mage = 41.27, SD = 12.53) ranging in coaching experience and backgrounds completed an online questionnaire detailing their use of, and preference for different sources of coaching knowledge. First, a list of 16 sources was formulated through a review of the literature (including the original 7 sources) and consultation with both varsity coaches and sport coach researchers. The findings demonstrated that interacting with other coaches, learning by doing, and observing other coaches were identified as the top three actual sources of coaching knowledge. In contrast, coaches top three preferred sources of coaching knowledge were observing other coaches, interacting with other coaches, and having a coach mentor. Exploratory analyses also considered differences in actual and preferred sources across demographic characteristics. Although some small differences were noted, the distribution between groups were generally comparable for the top actual and preferred knowledge sources reported by coaches. These results replicated some of the initial findings, but also found some important differences. In Study 2, a selected sample of competition-development coaches from Study 1 (N = 15) participated in an individual follow-up interview to probe deeper into their reported knowledge sources. Five distinct narrative types were identified from the qualitative interviews, representing coaches in different career trajectories: (1) recent elite athletes, (2) parent coaches, (3) coach developers, (4) teacher coaches and (5) experienced coaches. Regardless of background and life experiences, coaches expressed a strong preference for unstructured learning. However, the reasons for coaches` preferences appeared to differ based on lifestyle, learning styles, and perceived barriers. Overall, participants explained that coaches are social beings who find it more feasible to learn through hands-on experience with real-time interactions. Taken together, the results of two studies introduce newly identified and updated sources of knowledge for coaches and highlight some discrepancies between how coaches actually learn and how they would prefer to learn. Although similarities and differences emerged in comparison with the findings of Erickson and colleagues (2008), there appears to be a movement towards more unstructured learning experiences despite the fact that technology has permeated the coaching world. Further, the narratives shed light on coaches` preferences and the barriers to some forms of knowledge acquisition such as the lack of feasibility (e.g., time and cost) associated with some formalized coach education programs. Collectively, these findings offer many theoretical and practical implications for coaches, coach developers, coaching and sport psychology researchers, and sport organizations.